2015
DOI: 10.1111/tra.12315
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Temporal Regulation of RET Isoform Internalization: Roles of Clathrin and AP2

Abstract: The RET receptor tyrosine kinase (RTK) contributes to kidney and nervous system development, and is implicated in a number of human cancers.RET is expressed as two protein isoforms, RET9 and RET51, with distinct interactions and signaling properties that contribute to these processes.RET isoforms are internalized from the cell surface into endosomal compartments in response to glial cell line-derived neurotropic factor (GDNF) ligand stimulation but the specific mechanisms of RET trafficking remain to be elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 74 publications
(124 reference statements)
6
51
0
Order By: Relevance
“…Because of pair to pair variability, we compare ret hu2846 mutant embryos to sibling controls within clutches from individual pair matings. To test if a particular Ret isoform was required for pLLg axon outgrowth, we injected ret hu2846 mutant and sibling embryos from individual clutches with in vitro transcribed human Ret isoform mRNA tagged with mCherry, either RET9mcherry or RET51-mcherry 18 , at the one-cell stage and assayed at 3 dpf for axon length, measuring the shortest pLLg axon bundle in the embryo as a conservative measure of axon extension rescue ( Fig. 2C,D).…”
Section: The Ret51 Isoform Is Required For Lateral Line Axon Extensionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of pair to pair variability, we compare ret hu2846 mutant embryos to sibling controls within clutches from individual pair matings. To test if a particular Ret isoform was required for pLLg axon outgrowth, we injected ret hu2846 mutant and sibling embryos from individual clutches with in vitro transcribed human Ret isoform mRNA tagged with mCherry, either RET9mcherry or RET51-mcherry 18 , at the one-cell stage and assayed at 3 dpf for axon length, measuring the shortest pLLg axon bundle in the embryo as a conservative measure of axon extension rescue ( Fig. 2C,D).…”
Section: The Ret51 Isoform Is Required For Lateral Line Axon Extensionmentioning
confidence: 99%
“…Live imaging of RET51/Jip3 retrograde co-transport as well as the disruption of RET51 retrograde axonal transport and pRet localization followed by loss of Jip3, suggests Ret51 retrograde transport may be required for this signaling role. In other cell types, Ret51 is much more rapidly internalized from the plasma membrane and differentially ubiquitylated compared to Ret9 18,40 . In mouse sympathetic neuron culture, Ret51 is more rapidly degraded in axon terminals compared to Ret9 following GDNF treatment 16 .…”
Section: A Specific Role For Ret51 Signaling In Pioneer Axon Outgrowthmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, RET9 and RET51 recruit distinct signalling and regulatory protein complexes (Tsui-Pierchala et al, 2002). We have previously shown that RET9 and RET51 differ in maturation, subcellular localization and protein trafficking after ligand stimulation (Crupi et al, 2015a;Richardson et al, 2012), suggesting that isoform-specific regulatory mechanisms also contribute to functional differences. In response to ligand, RET receptors at the cell surface are internalized into the endosomal network via clathrin-coated pits (CCPs) (Crupi et al, 2015a;Richardson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%